Komunikasi Keluarga dan Perilaku Konsumtif Remaja: Kajian Literatur - Adeni, Susri; Pratiwi, Ismayanti; Harahap, Machyudin Agung (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study aims to explore the relationship between family communication and adolescent consumptive behavior through a systematic literature review. The phenomenon of consumptive behavior among adolescents is increasingly evident, driven by digital technology and globalization, which influence lifestyle and social values. Adolescence is a critical stage where identity formation, social acceptance needs, and mass media exposure significantly shape consumption patterns. Consumptive behavior among adolescents is characterized by impulsive buying, brand dependence, overspending, and a lifestyle centered on self-image. Family communication plays a vital role in shaping adolescents' consumption values and behaviors. Effective communication, marked by openness, emotional warmth, reflective discussion, and value consistency, can mitigate excessive consumptive behavior. Conversely, instructional or coercive communication often leads to adolescent resistance and compensatory consumptive behaviors. Contextual factors such as family socio-economic status, parental education, cultural values, emotional relationships, and social media exposure also influence the effectiveness of family communication. This study concludes that high-quality family communication can foster adolescents' critical and responsible consumption literacy. Practical implications highlight the need for education targeting parents, schools, and policymakers to enhance family communication skills in supporting healthy adolescent consumption behavior